Հաղարծնավանքի դավանաբանական կողմնորոշման շուրջ - Աշոտ Մանուչարյան (ՀՀ ԳԱԱ հրատ.)
В свое время некоторые армянские ученые, не углубляясь в изучение двух фактов, высеченных в Агарцинском монастыре, поспешно полагали, что этот монастырь в определенный период последовал халкидонскому вероисповеданию. Previously several Armenian scholars, without having studied thoroughly two lapidary inscriptions carved on the monastery wall, wrongly assumed that Haghartsin monastery followed the Chalcedonian faith at a certain period of time.
Keywords: Medieval History; History; D History